Catalyst for preparing ethylbenzene by dehydrogenation of butadiene dimer and preparation method thereof

By coating nano sharp tin-type TiO2 on the surface of Al2O3 and adding Sn additives to the Pt-based catalyst, the problems of high reaction temperature of the Pt-based catalyst and catalyst deactivation are solved, and the efficient conversion of butadiene dimer into ethylbenzene is achieved.

CN119588342AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311141478.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-11
Estimated Expiration
2043-09-06

AI Technical Summary

Technical Problem

In the prior art, the reaction temperature of the Pt-based catalyst is relatively high, and carbon deposits are easily generated on the surface of the catalyst, resulting in the deactivation of the catalyst, and the butadiene dimer cannot be effectively utilized.

Method used

By coating nano sharp tin type TiO2 on the surface of Al2O3, a highly active hydroxyl group is generated, and the additive Sn is added to the Pt-based catalyst to modify the defect position on the surface of the active metal Pt, thereby improving the dispersion of Pt and the activity of the catalyst.

Benefits of technology

The Pt-Sn/Al2O3-TiO2 catalyst that maintains high reaction activity at a lower reaction temperature is achieved, which improves the conversion rate of butadiene dimer and the selectivity of ethylbenzene, and has good industrial application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation processes, in particular to a catalyst for preparing ethylbenzene by dehydrogenation of butadiene dimer, and a preparation method and application of the catalyst. Aiming at the defects in the prior art, the invention aims to improve the concentration of high-activity hydroxyl groups on the surface of a catalyst carrier, a layer of nano anatase tin type TiO2 is coated on the surface of Al2O3, and the anatase tin type TiO2 can generate high-activity hydroxyl groups under the irradiation of ultraviolet light. Meanwhile, the auxiliary Sn is added into the Pt-based catalyst, so that defect sites on the surface of active metal Pt can be modified, the dispersity of Pt can be improved, adsorption to an ethylbenzene product can be reduced, generation of byproducts can be inhibited, and the purpose of improving the activity and selectivity of the catalyst can be achieved. The catalyst has good reaction performance, under the condition that the reaction temperature is 303-335 DEG C, the conversion rate of butadiene dimer is larger than 90%, the ethylbenzene selectivity is larger than 92%, and the catalyst has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalyst preparation technology, and in particular to a catalyst for preparing ethylbenzene by dehydrogenating butadiene dimer, and a preparation method and application of the catalyst. Background Art

[0002] Butadiene dimer is a byproduct of butadiene extraction unit in large petrochemical enterprises, and its output is about 1% of the total butadiene. Domestic butadiene units mainly use N,N-dimethylformamide (DMF) solvent as an extractant to purify butadiene products. A small amount of butadiene will polymerize in DMF solvent to form dimers, the main component of which is 4-vinylcyclohexene (4-Vinyl-1-cyclohexene). At present, there is no good way to utilize butadiene dimer. It is mainly used as light fuel oil. However, since it contains a large amount of water, it must be dehydrated before combustion, otherwise it will cause the solution to boil suddenly, which poses a high safety hazard. At the same time, it has a strong fishy odor, which will bring a strong odor to the device site during use or long-term storage, and will also cause damage to the health of the staff. Ethylbenzene is a raw material for the synthesis of styrene, and its market consumption is large. At present, ethylbenzene is mainly prepared by alkylation of benzene and ethylene. Due to the high prices of benzene and ethylene, this preparation route is not economical. Considering the market usage and process safety, dehydrogenating butadiene dimer to produce ethylbenzene can not only improve the utilization value of butadiene dimer, but also provide an economical ethylbenzene synthesis route.

[0003] Butadiene dimer will undergo dehydrogenation reaction to produce ethylbenzene under the action of precious metal Pt-based catalyst. This reaction includes two steps: (1) 4-vinylcyclohexene directly removes four hydrogen atoms on the catalyst surface to produce styrene; (2) the vinyl group in the styrene molecule is added with the hydrogen atoms removed to produce ethylbenzene. Public documents (Petrochemicals, 1995(08):545-548) show that the use of precious metal Pt-based catalysts can achieve higher butadiene dimer conversion rates and ethylbenzene selectivity. For example, on Pt / Al2O3 catalysts, the butadiene dimer conversion rate can reach 80%, and the ethylbenzene selectivity remains above 90%.

[0004] However, in the prior art, the reaction temperature of Pt-based catalysts is high, and carbon deposits are easily generated on the catalyst surface, resulting in catalyst deactivation. Therefore, the development of Pt-based catalysts with higher reaction activity at lower reaction temperatures has always been a research focus. Pt-based catalysts mainly play a catalytic role through hydrogen overflow. The four hydrogen atoms on the cyclohexene in the 4-vinylcyclohexene molecule are first adsorbed on the Pt surface, and then overflow to the hydroxyl groups on the surface of the Al2O3 carrier. Therefore, the hydroxyl activity on the surface of the Al2O3 carrier directly affects the hydrogen overflow rate. The higher the hydroxyl activity, the faster the hydrogen overflow rate. Studies have found that there are generally four types of hydroxyl groups on the surface of the Al2O3 carrier, and the surface concentration of the hydroxyl group with the highest stretching vibration frequency is the smallest. Therefore, measures can be taken to increase the concentration of highly active hydroxyl groups on the surface of the Al2O3 carrier, thereby increasing the hydrogen overflow rate, in order to achieve the purpose of improving the catalyst reaction activity and reducing the reaction temperature. Summary of the invention

[0005] In view of the defects of the prior art, the present invention aims to increase the concentration of highly active hydroxyl groups on the surface of the catalyst carrier by coating a layer of nano-sharp tin-type TiO2 on the surface of Al2O3, which will produce highly active hydroxyl groups under ultraviolet light. At the same time, adding an auxiliary agent Sn to the Pt-based catalyst can modify the defect sites on the surface of the active metal Pt, improve the dispersion of Pt, reduce the adsorption of ethylbenzene products, and inhibit the generation of by-products, thereby achieving the purpose of improving the activity and selectivity of the catalyst.

[0006] The purpose of the present invention is to provide a Pt-Sn / Al2O3-TiO2 catalyst with a carrier surface rich in highly active hydroxyl groups and a preparation method thereof. The mass fraction of Pt is 0.2-0.8%, the mass fraction of Sn is 0.1-0.4%, the mass fraction of Al2O3 is 83.8%-94.8%, and the mass fraction of TiO2 is 4.9-15.0%. Chloroplatinic acid aqueous solution, tin tetrachloride aqueous solution, γ-Al2O3 and anastomosing TiO2 are all commercially available.

[0007] The present invention provides a method for preparing a Pt-Sn / Al2O3-TiO2 catalyst having a carrier surface rich in highly active hydroxyl groups, comprising the following steps:

[0008] (1) Dispersing γ-Al2O3 in nano-sharp tin type TiO2 hydrosol and drying under stirring;

[0009] (2) sending the dried γ-Al2O3 coated with TiO2 to a muffle furnace for calcination;

[0010] (3) irradiating the calcined solid with ultraviolet light to obtain an Al2O3-TiO2 composite carrier;

[0011] (4) immersing equal volumes of the Al2O3-TiO2 composite support in an aqueous solution of chloroplatinic acid and tin tetrachloride and drying under stirring;

[0012] (5) sending the dried solid into a muffle furnace for calcination to obtain PtO2-SnO2 / Al2O3-TiO2;

[0013] (6) PtO2-SnO2 / Al2O3-TiO2 is fed into a tubular furnace and reduced with hydrogen to obtain a Pt-Sn / Al2O3-TiO2 catalyst.

[0014] The γ-Al2O3 in step (1) has a specific surface area of ​​120 to 250 m 2 / g, spherical particles with a particle size of 0.5 to 2.5 mm;

[0015] The nano-sharp tin type TiO2 hydrosol described in step (1) has an average particle size of 10 to 25 nm and a TiO2 content of 5 to 15%;

[0016] The stirring and drying temperature in step (1) is 80 to 150° C., and the drying time is 8 to 15 hours;

[0017] The muffle furnace roasting temperature in step (2) is 550-650° C., and the roasting time is 4-8 hours;

[0018] The ultraviolet light irradiation time in step (3) is 4 to 10 hours;

[0019] The mass fraction of Pt in the aqueous solution of chloroplatinic acid and tin tetrachloride in step (4) is 0.2% to 0.8%, and the mass fraction of Sn is 0.1% to 0.4%;

[0020] The stirring and drying temperature in step (4) is 80 to 150° C., and the drying time is 8 to 15 hours;

[0021] The muffle furnace calcination temperature in step (5) is 550-650° C., and the calcination time is 4-8 hours;

[0022] The hydrogen reduction temperature in step (6) is 400-600° C., and the reduction time is 4-8 hours.

[0023] The method for applying the Pt-Sn / Al2O3-TiO2 catalyst with a carrier surface rich in highly active hydroxyl groups provided by the present invention is as follows: the catalyst is loaded into a reactor, the catalyst bed is first calcined at 200-250°C with nitrogen passing therethrough for 1-3 hours, and the nitrogen flow rate is 10-20 L / (g cath); then the reactor temperature is raised to 300-320°C, the butadiene dimer raw material pumped in is vaporized and mixed evenly with nitrogen before entering the catalyst bed. The vaporization temperature of butadiene dimer is 250-300°C, and the volume ratio of butadiene dimer to nitrogen after vaporization is 1:100-1:20; the reaction products are collected by a gas-liquid separator and analyzed.

[0024] The present invention provides a Pt-Sn / Al2O3-TiO2 catalyst with a carrier surface rich in highly active hydroxyl groups. The catalyst is applied to the dehydrogenation of butadiene dimer to produce ethylbenzene, which can effectively solve the defects of the prior art. The catalyst has good reaction performance. Under the reaction temperature of 303-335°C, the butadiene dimer conversion rate is greater than 90%, and the ethylbenzene selectivity is greater than 92%, and the catalyst has good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS DETAILED DESCRIPTION

[0025] The present invention is further described with the following examples. However, it is necessary to point out that the following examples are only used to further describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.

[0026] Embodiment 1:

[0027] The specific surface area of ​​20g is 120m 2 / g, γ-Al2O3 spherical particles with a particle size of 0.5mm are dispersed in 21.1g of nano-sharp tin-type TiO2 hydrosol with an average particle size of 10nm and a TiO2 content of 5%. The dispersed solution is stirred and dried at 80°C for 15h. The dried γ-Al2O3 coated with TiO2 is first sent to a muffle furnace for calcination at 550 degrees Celsius for 4h, and then irradiated with ultraviolet light for 4h to obtain an Al2O3-TiO2 composite carrier, in which the TiO2 content is 5%. An equal volume of 20g of the Al2O3-TiO2 carrier is immersed in an aqueous solution of 20.1mL of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.2% and the mass fraction of Sn is 0.1%. The impregnation liquid was first stirred and dried at 80°C for 15 hours, and then the dried solid was sent to a muffle furnace and calcined at 550 degrees Celsius for 4 hours. Finally, the calcined solid was sent to a tubular furnace and reduced with hydrogen at 400°C for 8 hours to obtain a Pt-Sn / Al2O3-TiO2 catalyst, in which the mass fraction of Pt was 0.2%, the mass fraction of Sn was 0.1%, the mass fraction of Al2O3 was 94.715%, and the mass fraction of TiO2 was 4.985%.

[0028] Comparative Example 1:

[0029] The specific surface area of ​​20g is 120m 2 / g, γ-Al2O3 spherical particles with a particle size of 0.5mm are immersed in 20.1mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.2% and the mass fraction of Sn is 0.1%. The impregnation solution is first stirred and dried at 80°C for 15h, and then the dried solid is first sent to a muffle furnace for calcination at 550°C for 4h, and finally the calcined solid is sent to a tubular furnace and reduced with hydrogen at 400°C for 8h to obtain a Pt-Sn / Al2O3 catalyst, in which the mass fraction of Pt is 0.2%, the mass fraction of Sn is 0.1%, and the mass fraction of Al2O3 is 99.7%.

[0030] 10 g of the catalysts prepared in Example 1 and Comparative Example 1 were respectively loaded into the reactor, and the catalyst bed was first calcined at 200° C. for 1 h with nitrogen flow rate of 10 L / (g cat h); then the reactor temperature is raised to 320°C, the butadiene dimer raw material pumped in is vaporized and mixed with nitrogen to enter the catalyst bed, the vaporization temperature of butadiene dimer is 250°C, the pumping flow rate of butadiene dimer is 4.8g / h, and the volume ratio of butadiene dimer to nitrogen is 1:100; the reaction products are collected by gas-liquid separator and analyzed. The results show that the conversion rate of butadiene dimer of the catalyst prepared in Example 1 is 94.7% and the selectivity of ethylbenzene is 96.3% at a reaction temperature of 326°C; the conversion rate of butadiene dimer of the catalyst prepared in Comparative Example 1 is 83.6% and the selectivity of ethylbenzene is 91.2% at a reaction temperature of 321°C.

[0031] Embodiment 2:

[0032] The specific surface area of ​​20g is 250m 2 / g, γ-Al2O3 spherical particles with a particle size of 2.5mm are dispersed in 23.5g of nano-sharp tin-type TiO2 hydrosol with an average particle size of 25nm and a TiO2 content of 15%. The dispersed solution is stirred and dried at 150°C for 8h. The dried γ-Al2O3 coated with TiO2 is first sent to a muffle furnace for calcination at 650 degrees Celsius for 8h, and then irradiated with ultraviolet light for 10h to obtain an Al2O3-TiO2 composite carrier, in which the TiO2 content is 15%. 20g of the Al2O3-TiO2 carrier is immersed in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.8% and the mass fraction of Sn is 0.4%. The impregnation liquid was first stirred and dried at 150°C for 8 hours, and then the dried solid was sent to a muffle furnace and calcined at 650°C for 8 hours. Finally, the calcined solid was sent to a tubular furnace and reduced with hydrogen at 600°C for 4 hours to obtain a Pt-Sn / Al2O3-TiO2 catalyst, in which the mass fraction of Pt was 0.8%, the mass fraction of Sn was 0.4%, the mass fraction of Al2O3 was 83.98%, and the mass fraction of TiO2 was 14.82%.

[0033] Comparative Example 2:

[0034] The specific surface area of ​​20g is 250m 2 / g, γ-Al2O3 spherical particles with a particle size of 2.5mm are immersed in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.8% and the mass fraction of Sn is 0.4%. The impregnation solution is first stirred and dried at 150°C for 8h, and then the dried solid is first sent to a muffle furnace for calcination at 650°C for 8h, and finally the calcined solid is sent to a tubular furnace and reduced with hydrogen at 600°C for 4h to obtain a Pt-Sn / Al2O3 catalyst, in which the mass fraction of Pt is 0.8%, the mass fraction of Sn is 0.4%, and the mass fraction of Al2O3 is 98.8%.

[0035] 10 g of the catalysts prepared in Example 2 and Comparative Example 2 were respectively loaded into the reactor, and the catalyst bed was first calcined at 250° C. for 3 h with nitrogen flow rate of 20 L / (g cath); then the reactor temperature is raised to 300°C, the butadiene dimer raw material pumped in is vaporized and mixed with nitrogen to enter the catalyst bed, the vaporization temperature of butadiene dimer is 300°C, the pumping flow rate of butadiene dimer is 48.3g / h, and the volume ratio of butadiene dimer to nitrogen is 1:20; then the reaction product is collected by gas-liquid separator and analyzed. The results show that the conversion rate of butadiene dimer of the catalyst prepared in Example 2 is 90.2% and the selectivity of ethylbenzene is 98.6% at a reaction temperature of 303°C; the conversion rate of butadiene dimer of the catalyst prepared in Comparative Example 2 is 47.2% and the selectivity of ethylbenzene is 96.2% at a reaction temperature of 300°C.

[0036] Embodiment 3:

[0037] The specific surface area of ​​20g is 210m 2 / g, γ-Al2O3 spherical particles with a particle size of 1.0mm are dispersed in 21.0g of nano-sharp tin-type TiO2 hydrosol with an average particle size of 17nm and a TiO2 content of 13%. The dispersed solution is stirred and dried at 120°C for 10h. The γ-Al2O3 coated with TiO2 after drying is first sent to a muffle furnace for calcination at 600°C for 6h, and then irradiated with ultraviolet light for 6h to obtain an Al2O3-TiO2 composite carrier, in which the TiO2 content is 12%. 20g of the Al2O3-TiO2 carrier is immersed in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.6% and the mass fraction of Sn is 0.3%. The impregnation liquid was first stirred and dried at 120°C for 10 hours, and then the dried solid was sent to a muffle furnace for calcination at 600°C for 6 hours. Finally, the calcined solid was sent to a tubular furnace and reduced with hydrogen at 500°C for 6 hours to obtain a Pt-Sn / Al2O3-TiO2 catalyst, in which the mass fraction of Pt was 0.6%, the mass fraction of Sn was 0.3%, the mass fraction of Al2O3 was 87.208%, and the mass fraction of TiO2 was 11.892%.

[0038] Comparative Example 3:

[0039] The specific surface area of ​​20g is 210m 2 / g, γ-Al2O3 spherical particles with a particle size of 1.0mm are immersed in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, in which the mass fraction of Pt is 0.6% and the mass fraction of Sn is 0.3%. The impregnation solution is first stirred and dried at 120°C for 10 hours, and then the dried solid is first sent to a muffle furnace for calcination at 600°C for 6 hours, and finally the calcined solid is sent to a tubular furnace and reduced with hydrogen at 500°C for 6 hours to obtain a Pt-Sn / Al2O3 catalyst, in which the mass fraction of Pt is 0.6%, the mass fraction of Sn is 0.3%, and the mass fraction of Al2O3 is 99.1%.

[0040] 10 g of the catalysts prepared in Example 3 and Comparative Example 3 were respectively loaded into the reactor, and the catalyst bed was first calcined at 200° C. for 2 h with nitrogen flow rate of 13 L / (g cat h); then the reactor temperature is raised to 320°C, the butadiene dimer raw material pumped in is vaporized and mixed with nitrogen to enter the catalyst bed, the vaporization temperature of butadiene dimer is 280°C, the pumping flow rate of butadiene dimer is 10.5g / h, and the volume ratio of butadiene dimer to nitrogen is 1:60; the reaction products are collected by gas-liquid separator and analyzed. The results show that the conversion rate of butadiene dimer of the catalyst prepared in Example 3 is 98.7% and the selectivity of ethylbenzene is 97.2% at a reaction temperature of 330°C; the conversion rate of butadiene dimer of the catalyst prepared in Comparative Example 3 is 88.6% and the selectivity of ethylbenzene is 93.1% at a reaction temperature of 324°C.

[0041] Embodiment 4:

[0042] 20g of the Al2O3-TiO2 carrier prepared in Example 3 was impregnated in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, wherein the mass fraction of Pt in the aqueous solution was 0.8% and the mass fraction of Sn was 0.1%. The impregnation solution was first stirred and dried at 120°C for 10h, and then the dried solid was first sent to a muffle furnace for calcination at 600°C for 6h, and finally the calcined solid was sent to a tubular furnace for reduction with hydrogen at 500°C for 6h to obtain a Pt-Sn / Al2O3-TiO2 catalyst, wherein the mass fraction of Pt was 0.8%, the mass fraction of Sn was 0.1%, the mass fraction of Al2O3 was 87.208%, and the mass fraction of TiO2 was 11.892%.

[0043] The catalyst prepared in Example 4 was evaluated according to the reaction conditions of the catalyst prepared in Example 3. The results showed that at a reaction temperature of 327° C., the catalyst prepared in Example 4 had a butadiene dimer conversion rate of 95.7% and an ethylbenzene selectivity of 92.2%.

[0044] Embodiment 5:

[0045] 20g of the Al2O3-TiO2 carrier prepared in Example 3 was impregnated in 20.1mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, wherein the mass fraction of Pt in the aqueous solution was 0.2% and the mass fraction of Sn was 0.4%. The impregnation solution was first stirred and dried at 120°C for 10h, and then the dried solid was first sent to a muffle furnace for calcination at 600°C for 6h, and finally the calcined solid was sent to a tubular furnace for reduction with hydrogen at 500°C for 6h to obtain a Pt-Sn / Al2O3-TiO2 catalyst, wherein the mass fraction of Pt was 0.2%, the mass fraction of Sn was 0.4%, the mass fraction of Al2O3 was 87.472%, and the mass fraction of TiO2 was 11.928%.

[0046] The catalyst prepared in Example 5 was evaluated according to the reaction conditions of the catalyst prepared in Example 3. The results showed that at a reaction temperature of 321° C., the catalyst prepared in Example 5 had a butadiene dimer conversion rate of 91.7% and an ethylbenzene selectivity of 92.3%.

[0047] Embodiment 6:

[0048] 20g of the Al2O3-TiO2 carrier prepared in Example 1 was impregnated in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, wherein the mass fraction of Pt in the aqueous solution was 0.6% and the mass fraction of Sn was 0.3%. The impregnation solution was first stirred and dried at 120°C for 10h, and then the dried solid was first sent to a muffle furnace for calcination at 600°C for 6h, and finally the calcined solid was sent to a tubular furnace for reduction with hydrogen at 500°C for 6h to obtain a Pt-Sn / Al2O3-TiO2 catalyst, wherein the mass fraction of Pt was 0.6%, the mass fraction of Sn was 0.3%, the mass fraction of Al2O3 was 94.145%, and the mass fraction of TiO2 was 4.955%.

[0049] The catalyst prepared in Example 6 was evaluated according to the reaction conditions of the catalyst prepared in Example 3. The results showed that at a reaction temperature of 326° C., the catalyst prepared in Example 6 had a butadiene dimer conversion rate of 92.6% and an ethylbenzene selectivity of 95.1%.

[0050] Embodiment 7:

[0051] 20g of the Al2O3-TiO2 carrier prepared in Example 2 was impregnated in 20.2mL of an aqueous solution of chloroplatinic acid and tin tetrachloride, wherein the mass fraction of Pt in the aqueous solution was 0.6% and the mass fraction of Sn was 0.3%. The impregnation solution was first stirred and dried at 120°C for 10h, and then the dried solid was first sent to a muffle furnace for calcination at 600°C for 6h, and finally the calcined solid was sent to a tubular furnace for reduction with hydrogen at 500°C for 6h to obtain a Pt-Sn / Al2O3-TiO2 catalyst, wherein the mass fraction of Pt was 0.6%, the mass fraction of Sn was 0.3%, the mass fraction of Al2O3 was 84.235%, and the mass fraction of TiO2 was 14.865%.

[0052] The catalyst prepared in Example 7 was evaluated according to the reaction conditions of the catalyst prepared in Example 3. The results showed that at a reaction temperature of 323° C., the catalyst prepared in Example 7 had a butadiene dimer conversion rate of 90.7% and an ethylbenzene selectivity of 96.3%.

[0053] Embodiment 8:

[0054] 10 g of the catalyst prepared in Example 3 was loaded into the reactor, and the catalyst bed was first calcined at 200°C for 2 h with nitrogen flow rate of 13 L / (g cat h); then the reactor temperature was raised to 310°C, the butadiene dimer raw material pumped in was vaporized and mixed with nitrogen and then evenly entered the catalyst bed, the vaporization temperature of butadiene dimer was 280°C, the pumping flow rate of butadiene dimer was 10.5g / h, and the volume ratio of butadiene dimer to nitrogen was 1:60; the reaction products were collected by gas-liquid separator and analyzed. The results showed that the catalyst prepared in Example 3 had a conversion rate of butadiene dimer of 94.6% and an ethylbenzene selectivity of 96.1% at a reaction temperature of 314°C.

[0055] Embodiment 9:

[0056] 10 g of the catalyst prepared in Example 3 was loaded into the reactor, and the catalyst bed was first calcined at 200°C for 2 h with nitrogen flow rate of 13 L / (g cat h); then the reactor temperature was raised to 330°C, the butadiene dimer raw material pumped in was vaporized and mixed with nitrogen and then evenly entered the catalyst bed, the vaporization temperature of butadiene dimer was 280°C, the pumping flow rate of butadiene dimer was 10.5g / h, and the volume ratio of butadiene dimer to nitrogen was 1:60; the reaction products were collected by gas-liquid separator and analyzed. The results showed that the catalyst prepared in Example 3 had a conversion rate of butadiene dimer of 99.1% and an ethylbenzene selectivity of 93.1% at a reaction temperature of 335°C.

[0057] Embodiment 10:

[0058] 10 g of the catalyst prepared in Example 3 was loaded into the reactor, and the catalyst bed was first calcined at 200°C for 2 h with nitrogen flow rate of 18 L / (g cat h); then the reactor temperature was raised to 320°C, the butadiene dimer raw material pumped in was vaporized and mixed with nitrogen and then evenly entered the catalyst bed, the vaporization temperature of butadiene dimer was 280°C, the pumping flow rate of butadiene dimer was 10.5g / h, and the volume ratio of butadiene dimer to nitrogen was 1:83.1; the reaction products were collected by gas-liquid separator and analyzed. The results showed that the catalyst prepared in Example 3 had a conversion rate of butadiene dimer of 91.7% and an ethylbenzene selectivity of 97.2% at a reaction temperature of 326°C.

[0059] Embodiment 11:

[0060] 10 g of the catalyst prepared in Example 3 was loaded into the reactor, and the catalyst bed was first calcined at 200° C. for 2 h with nitrogen flow rate of 10 L / (g cat h); then the reactor temperature was raised to 320°C, the butadiene dimer raw material pumped in was vaporized and mixed with nitrogen and then evenly entered the catalyst bed, the vaporization temperature of butadiene dimer was 280°C, the pumping flow rate of butadiene dimer was 10.5g / h, and the volume ratio of butadiene dimer to nitrogen was 1:46.2; the reaction products were collected by gas-liquid separator and analyzed. The results showed that the catalyst prepared in Example 3 had a conversion rate of butadiene dimer of 99.3% and an ethylbenzene selectivity of 92.3% at a reaction temperature of 333°C.

Claims

1. A Pt-Sn / Al2O3-TiO2 catalyst, characterized in that: Al2O3-TiO2 is used as a composite carrier of the catalyst, and Pt and Sn are loaded on the composite carrier; the mass fraction of Pt in the Pt-Sn / Al2O3-TiO2 catalyst is 0.2-0.8%, the mass fraction of Sn is 0.1-0.4%, the mass fraction of Al2O3 is 83.8%-94.8%, and the mass fraction of TiO2 is 4.9-15.0%.

2. The catalyst according to claim 1, characterized in that The mass fraction of the Al2O3-TiO2 composite carrier is 98.8-99.7%, and the mass fraction of TiO2 is 5%-15% of the Al2O3-TiO2 composite carrier.

3. The catalyst according to claim 1, characterized in that The mass fraction of Pt in the catalyst is 0.6%, the mass fraction of Sn is 0.3%, the mass fraction of Al2O3 is 87.2%, and the mass fraction of TiO2 is 11.8%; or the mass fraction of Pt in the catalyst is 0.2%, the mass fraction of Sn is 0.4%, the mass fraction of Al2O3 is 87.5%, and the mass fraction of TiO2 is 11.9%.

4. A method for preparing the catalyst according to claims 1 to 3, characterized in that: The preparation steps are as follows: (1) Dispersing γ-Al2O3 in nano-sharp tin-type TiO2 aqueous sol; (2) After drying, the obtained γ-Al2O3 coated with TiO2 is calcined; (3) irradiating the calcined solid with ultraviolet light to obtain an Al2O3-TiO2 composite carrier; (4) impregnating the Al2O3-TiO2 composite support in a platinum salt and tin salt solution; (5) After drying, the obtained solid is calcined to obtain PtO2-SnO2 / Al2O3-TiO2; (6) The prepared PtO2-SnO2 / Al2O3-TiO2 is reduced to obtain a Pt-Sn / Al2O3-TiO2 catalyst.

5. The preparation method according to claim 4, characterized in that: The γ-Al2O3 in step (1) has a specific surface area of ​​120 to 250 m 2 / g, particles with a particle size of 0.5 to 2.5 mm; the average particle size of the nano sharp tin type TiO2 hydrosol is 10 to 25 nm, and the TiO2 content is 5 to 15%.

6. The preparation method according to claim 4, characterized in that: The mass fraction of Pt in the aqueous solution of platinum salt and tin salt described in step (4) is 0.2% to 0.8%, and the mass fraction of Sn is 0.1% to 0.4%.

7. The preparation method according to claim 4, characterized in that: The calcination process described in step (2) and step (5) has a temperature of 550-650° C. and a calcination time of 4-8 hours.

8. The preparation method according to claim 4, characterized in that: The ultraviolet light irradiation process described in step (3) lasts for 4 to 10 hours.

9. The preparation method according to claim 4, characterized in that: The process of reducing PtO2-SnO2 / Al2O3-TiO2 in step (6) is carried out by using hydrogen, the hydrogen temperature is 400-600°C, and the reduction time is 4-8h.

10. Use of the catalyst according to claims 1 to 3 or the catalyst prepared by the preparation method according to claims 4 to 9, characterized in that: It is used in the dehydrogenation of butadiene dimer to produce ethylbenzene.

Citation Information

Patent Citations

  • Load type Pt / TiO2 / Al2O3 fiber composite photocatalyst and preparation method thereof

    CN102133524A

  • Processes for making ethanol or ethyl acetate from acetic acid using bimetallic catalysts

    CN102378647A

  • Platinum catalyst supported on double-oxide composite carrier and preparation method and application of platinum catalyst

    CN104148060A

  • Catalyst for preparing olefin by dehydrogenating low-carbon alkane and preparation method of catalyst

    CN104148062A

  • Nanometer diamond supported platinum-tin bimetallic catalyst and preparation method thereof, and applications of catalyst in direct dehydrogenation of n-butane

    CN109174093A